Templates of expected measurement uncertainties for average prompt and total fission neutron multiplicities - Neudecker Denise; Carlson Allan D.; Croft Stephen; Devlin Matthew; Kelly Keegan J.; Lovell Amy E.; Marini Paola; Taieb Julien (EPJ Nuclear Sciences & Technologies, 2023)
In this paper, we provide templates of measurement uncertainty sources expected to appear for average prompt- and total-fission neutron multiplicities,